Crisis economics : a crash course in the future of finance - Roubini, Nouriel; Mihm, Stephen, 1968- (New York : Penguin Press, 2010)
This myth-shattering book reveals the methods Roubini used to foretell the current crisis before other economists saw it coming and shows how those methods can help to make sense of the present and prepare for the future.
Includes bibliographical references (p. [329]-336) and index.
rpm 03/05/13
Loans
Keywords: Financial crises; Business cycles; Economics